The Effect of a Counseling Program on Acquiring Study Skills among Fourth-Year Middle School Pupils - NOUR EL HOUDA , LEGLIB; Meddour , Leila (Journal of Ecohumanism, 2026)
The current study aimed to reveal the effect of a counseling program on acquiring study skills among fourth-year middle school pupils. The study included a sample of (10) male and female fourth-year middle school pupils, who were selected intentionally. The study relied on the quasi-experimental one-group approach. The study tools consisted of: the counseling program designed by the researcher, and the Study Skills Scale prepared by Hafiz Nabil Ibrahim et al. (2014). The statistical treatment of the study hypotheses was carried out using the statistical analysis program SPSS v20. The study reached the following results: there is an effective impact of the counseling program on acquiring study skills, as the results indicated the presence of statistically significant differences after exposure to the program sessions between the pre-measurement scores and the post-measurement scores among the members of the counseling group, in favor of the post-measurement scores, with no statistically significant differences between the post-measurement scores and the follow-up measurement scores, which confirms the effectiveness of the counseling program.